Periostin induces proliferation of human autosomal dominant polycystic kidney cells through α(V)-integrin receptor - Wallace, Darren P. (American Physiological Society, 2008)
Progressive renal enlargement due to the growth of innumerable fluid-filled cysts is a central pathophysiological feature of autosomal dominant polycystic kidney disease (ADPKD). These epithelial neoplasms enlarge slowly and damage noncystic parenchyma by mechanisms that have not been clearly defined. In a microarray analysis of cultured human ADPKD cyst epithelial cells, periostin mRNA was overexpressed 15-fold compared with normal human kidney (NHK) cells. Periostin, initially identified in osteoblasts, is not expressed in normal adult kidneys but is expressed transiently during renal development. We found periostin in cyst-lining cells in situ in the extracellular matrix adjacent to the cysts and within cyst fluid. ADPKD cells secreted periostin across luminal and basolateral plasma membranes. Periostin increased proliferation of cyst epithelial cells 27.9 ± 3.1% (P < 0.001) above baseline and augmented in vitro cyst growth but did not affect proliferation of normal renal cells. Expression of α(V)-integrin, a periostin receptor, was ninefold higher in ADPKD cells compared with NHK cells, and antibodies that block α(V)-integrin inhibited periostin-induced cell proliferation. We conclude that periostin is a novel autocrine mitogen secreted by mural epithelial cells with the potential to accelerate cyst growth and promote interstitial remodeling in ADPKD.